Pengaturan Penyebarluasan Pornografi Pada Media Sosial Ditinjau Dari Undang-Undang Informasi Dan Transaksi Elektronik - Petan, Putri Yuniastini; Yohanes, Saryono; Lamataro, Cyrilius W T (Law Faculty, Nusa Cendana University, 2025)
This study aims to analyze the regulation of pornography dissemination on social media under the Electronic Information and Transactions Law (EIT Law). In the digital era, technological advancements have brought both positive and negative impacts, including the dissemination of content violating social norms, such as pornography. This research adopts a normative juridical approach, focusing on the legal review of the EIT Law's application in addressing this issue. The findings reveal that the EIT Law, in its original form (Law Number 11 of 2008) and its subsequent amendments (Law Number 19 of 2016 and Law Number 1 of 2024), explicitly prohibits the dissemination of pornography through electronic systems. The amendments emphasize the responsibility of electronic system providers to remove illegal content and introduce stricter sanctions for offenders.Moreover, the study identifies challenges in implementation, such as low public legal awareness and technological limitations in detecting illegal content. This research provides recommendations for the government, electronic system providers, and the public to collaborate in creating a safer digital environment, particularly for children and teenagers. It is hoped that this study will contribute to the development of more effective legal policies in addressing the dissemination of pornography on social media.